O problema do pós-humanismo na filosofia contemporânea e o questionamento de Feenberg - Cecília de Sousa Neves (2022)
The techno-scientific revolution has provoked substantial changes of such a prodigious order that it has precipitated us into a new stage of human culture and a new kind of society. The debate about the profound political, ontological, ethical, and epistemological consequences of the absolute centrality of technology in shaping human experience and existence is still far from being well understood. Philosophy is largely on the margins of this broad debate, despite its fundamental role and invaluable potential contribution. Largely as a consequence of this gap and of philosophy's delay in formulating various problems posed by technology, two important agendas of thought have emerged in contemporary thought: transhumanism and posthumanism. These two reflexive byproducts of the technology Society launch current reflection on the consequences of technology's radical incidence on human and social experience. In the absence of philosophy, these agendas, especially transhumanism, elaborate the terms and influence the debate in both common sense and politics about how we should react to the interference of technology. In this scenario the main purpose of this work is to demonstrate the importance of philosophy, especially Feenberg's philosophy of technology, for the critical analysis of the transhumanist and posthumanist agendas. Although reflecting on these issues is not a central concern for Feenberg, we argue that his ideas on technology can be mobilized as critical elements of the transhumanist and posthumanist programs. This move will unveil an unprecedented approach to the problems and shortcomings of the transhumanist and posthumanist agendas. However, in order to do that - given the widespread confusion and instability in the debate about transhumanism and posthumanism - it was necessary to develop a broad mapping of transhumanist and posthumanist thought. This work, of a more descriptive nature, aims to present the main authors, seminal texts and main definitions in order to add to the debate, contributing to the establishment of a common understanding that would enable criticism and discussion. In the end, this dissertation should be understood as a contribution to the recognition of the philosophical dignity of the posthumanist and transhumanist programs, which will be addressed and criticized on the grounds of Andrew Feenberg's philosophy of technology.